Cegah Anemia dengan Gaya Hidup dan Gizi Seimbang - Theophylia Melisa Manumara; Ahmad Adhi Karya; Agustina Hermawati; Dewi Maharani; Irwan Anugrah Gulo; Isma Amalia Istiqomah; Lutfiana Nur Azizah; Siti Ai Aryati; Silvana Zahra Ramadani; Tri Murti Ningrum (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia is a health problem commonly experienced by adolescents, especially adolescent girls, due to an unbalanced diet, lack of iron intake, and minimal knowledge about nutrition and health. This condition has an impact on decreased concentration in learning, fitness, productivity, and increases the risk of infection. National data shows that the prevalence of anemia among adolescents reaches 32%, while in West Java it reaches 41.93%. Low coverage of iron tablets (TTD) consumption and lack of education cause anemia to remain a significant problem. Health education activities were conducted at SMA Negeri 5 Cimahi, involving 40 students, with the aim of increasing knowledge about anemia, its causes, effects, and prevention through a healthy lifestyle and balanced nutrition. The methods used included delivering material through presentations, distributing leaflets, discussions, ice breaking, and quizzes to reinforce understanding. The results of the activity showed that most students did not understand anemia before the education session, but after the education, there was an increase in knowledge as seen from the students' ability to answer questions and participate actively. This education session was effective in increasing students' awareness to apply a nutritious diet, get enough rest, exercise regularly, and comply with TTD consumption. Continuous education efforts in schools are important to prevent anemia in adolescents.